Study of Green Mussel Eating Habits (Perna Viridis) in Aleu Naga Waters, Banda Aceh - Abdullah Abbas, Muhammadar; Rusydi, Ichsan; Anna Misqa, Nur; Mellisa, Siska; Nurfadillah, Nurfadillah; Nanda Devira, Cut (Jurnal Kelautan dan Perikanan Indonesia, 2022)
Alue Naga waters is one of the coastal areas that have been used by the community as a residential area, a place for tourism, shrimp ponds, fish and fishing ground for oysters, green mussels and fish. Green mussels are one of the groups of the phylum molluscs in the class bivalves of the genus Perna and live attached to hard objects. This study aimed to analyze the food habits of the digestive tract of green mussels in the waters of Alue, Naga, Banda Aceh. This research was conducted from February to April 2022 in Alue Naga waters. Determination of the sampling location was carried out by purposive sampling with 3 stations. The method used for sampling green mussels was done by Random Sampling method and the number of samples taken was 45 samples, then preserved with 4% formalin. Food analysis was carried out at Marine Biology Laboratory, Faculty of Marine and Fisheries, Syiah Kuala University. The study, found that the food composition of green mussels consisted of 7 classes, namely: Baccillariophyceae class 45%, Chlorophyceae class 16%, Cyanophyceae class 19%, Dinophyceae class 3%, Coscinosiscophyceae class 10%, Zygnematophyceae class 3% and Euglenoidea 3%. Based on the highest IP (preponderance index) value, the main food of green mussels was obtained from the Baccillariophyceae class. The total length of green mussels was 79.56 mm and the average of intestinal length was 108.10 mm, the relative length of gut was 1.36. Based on the relative length of the intestine with a value of 1, green mussels are classified as omnivorous fish.Keywords: Green mussel, Food Habits, Gut